Business networks: development of actors’ strategic guidelines from the analysis of negotiation situations in Portugal - Falcão, Pedro Miguel Ribeiro de Almeida Fontes (2009)
The importance of relationships within business networks is increasing significantly in today’s more competitive and global world. The organization actors’ performance, especially in negotiation, is a key factor to consider in those relationships. But, on one hand, there is no structured approach from business network theory to negotiation and, on the other hand, the integrative negotiation main models and theories were not developed in the business network context. Within this environment, this dissertation’s objective is based on the identification and analysis of the actors’ main factors which impact negatively specific negotiation situations – negotiations with an initial perception of a potential win-win outcome, between different companies in a business network, and that ultimately lead to no agreement. The dissertation is focused only on the Portuguese market. We used a multiple-case design by analyzing thirty negotiation situations, focused on a sub-set of recent potential win-win negotiations between three different companies that did not reach an agreement. After identifying the main actors-related causes for not reaching an agreement, we identified the main factors and their relationships and derived learning outcomes from them. We believe we have made knowledge contributions to the Business Network Analysis and the Negotiations Analysis perspectives, and also to the general description of the business networks’ actors’ negotiation processes in Portugal, through five questions’ analysis and debate. There were limitations to the study and there are other areas or studies that can be further researched in the future.